The role of splicing factor mutations in the pathogenesis of the myelodysplastic syndromes. - Boultwood, J; Dolatshad, H; Varanasi, S; Yip, B; Pellagatti, A (2014)
Accurate pre-mRNA splicing by the spliceosome is a fundamental cellular mechanism required to remove introns that are present in most protein-coding transcripts. The recent discovery of a variety of somatic spliceosomal mutations in the myelodysplastic syndromes (MDS), a heterogeneous group of myeloid malignancies, has revealed a new leukemogenic pathway involving spliceosomal dysfunction. Spliceosome mutations are found in over half of all MDS patients and are likely founder mutations. The spliceosome mutations are highly specific to MDS and closely related conditions and, to some extent, appear to define distinct clinical phenotypes in MDS. The high frequency of mutations in different components of the RNA splicing machinery in MDS suggests that abnormal RNA splicing is the common consequence of these mutations. The identification of the downstream targets of the spliceosome mutations is an active area of research. Emerging data from the study of the MDS transcriptome suggests that spliceosomal mutations have effects on specific genes, including some previously shown to play a role in MDS pathogenesis. The effects of the spliceosomal mutations on RNA splicing and cell growth have been evaluated only in a limited context to date, however, and the determination of the impact of these mutations in primary human hematopoietic cells is essential in order to elucidate fully the molecular mechanism by which they contribute to MDS pathogenesis.